Implementing Intensive Listening Course to Improve Listening Score of Non-English Department Students - Norita Prasetya Wardhani; Ratna Ayu Dewi (IKIP PGRI Bojonegoro, 2022)
AbstractEnglish listening skill is not an easy skill for engineering students who mostly are not fully supported by their surroundings. They just listened something in English from songs or film with Indonesian subtitle. Facing English Proficiency Listening test is a scourge for the students because they are not confident enough and having less knowledge on listening English materials. To encounter that problem, the lecturer implemented an intensive listening course to improve the listening score of non-English department students. There were three objectives of this study. They were (1) to describe the process and implementation of intensive listening course to improve the listening score of non-English department students; (2) to describe the students’ listening scores after the intensive listening course was implemented; (3) to describe the surveys to find out the students’ opinions about this program. The participants of this research were 129 students of mechanical and civil engineering departments. This research used descriptive quantitative research as methodology. The data was gathered from the observation, students’ tests, and survey. This research showed that the non-English department students were given five test opportunities to achieve 423 points (as minimum score). The English course had 12 meetings, in which two of those meetings were focused on listening skill. They had 3 times of tests and the test result showed unsatisfactory scores. From those three tests, most of the students were able to answer correctly around 9 to 15 numbers, whereas the questions were 50 numbers. To improve the score, the students were given an additional listening intensive course. The lecturer gave more explanation and exercises to the students and it could improve students’ score. Most of the students were able to answer correctly around 16 to 31 numbers.Keywords: Non-English Students, Intensive Listening Course, Students’ Listening skill, Listening Strategies. AbstrakKeterampilan mendengarkan bahasa Inggris bukanlah keterampilan yang mudah bagi mahasiswa teknik yang sebagian besar tidak sepenuhnya didukung oleh lingkungannya. Mereka hanya mendengarkan sesuatu dalam bahasa Inggris dari lagu atau film dengan subtitle bahasa Indonesia. Menghadapi Tes Kecakapan Bahasa Inggris Listening merupakan momok bagi para mahasiswa karena mereka tidak cukup percaya diri dan kurang memiliki pengetahuan tentang materi listening bahasa Inggris. Untuk menghadapi masalah itu, dosen menerapkan kursus mendengarkan intensif untuk meningkatkan skor mendengarkan mahasiswa non-bahasa Inggris. Ada tiga tujuan dari penelitian ini. Mereka adalah (1) mendeskripsikan proses dan pelaksanaan kursus menyimak intensif untuk meningkatkan skor menyimak mahasiswa non-bahasa Inggris; (2) mendeskripsikan skor menyimak siswa setelah mata kuliah menyimak intensif dilaksanakan; (3) untuk mendeskripsikan survei untuk mengetahui pendapat siswa tentang program ini. Partisipan penelitian ini adalah 129 mahasiswa jurusan teknik mesin dan sipil. Penelitian ini menggunakan penelitian deskriptif kuantitatif sebagai metodologinya. Data dikumpulkan dari observasi, tes siswa, dan survei. Penelitian ini menunjukkan bahwa mahasiswa non-Bahasa Inggris diberi lima kesempatan tes untuk mencapai 423 poin (sebagai nilai minimum). Kursus bahasa Inggris memiliki 12 pertemuan, di mana dua dari pertemuan tersebut berfokus pada keterampilan mendengarkan. Mereka menjalani 3 kali tes dan hasil tes menunjukkan nilai yang tidak memuaskan. Dari ketiga tes tersebut, sebagian besar siswa mampu menjawab dengan benar sekitar 9 sampai 15 angka, sedangkan soal sebanyak 50 angka. Untuk meningkatkan skor, para siswa diberi kursus intensif mendengarkan tambahan. Dosen lebih banyak memberikan penjelasan dan latihan kepada mahasiswa sehingga dapat meningkatkan nilai mahasiswa. Sebagian besar siswa mampu menjawab dengan benar sekitar 16 sampai 31 angka.Kata kunci: Siswa Non-Bahasa Inggris, Kursus Intensive Listening, Keterampilan Mendengarkan Siswa, Strategi Mendengarkan